Buck boost converter control to accelerate cooling in hydrogen system coolers - Adi, Wasis Waskito; Akhiriyanto, Novan; Alson, Adi; Gunawan, Yohanes; Sahrin, Alfin; Utami, Erna (Politeknik Negeri Lhokseumawe, 2024)
The electrolysis process involves decomposing water (H₂O) into hydrogen gas (H₂) and oxygen gas (O₂), requiring substantial electrical power. This study utilized an electrolyzer with a maximum capacity of 7V and 40A, demanding 280 watts of power. Therefore, it requires a voltage of less than 7V but a high current of up to 40A, as the critical parameter for the electrolyzer in producing hydrogen is the electric current flowing through it. A buck-boost converter was implemented to adjust the voltage to operate a Thermoelectric Cooler (TEC) for temperature regulation. Over time, as the electrolyzer operates and consumes a high current, there is an increase in its temperature. The system successfully maintained the electrolyzer temperature below 35°C by adjusting the output voltage between 10-14V, with an input range of 21.62-21.65V. The cooling system achieved a temperature reduction of 1.06°C, demonstrating its effectiveness in stabilizing the electrolyzer’s performance, thus optimizing hydrogen production efficiency.